2005
DOI: 10.1210/jc.2004-1430
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Decrease Thyrotropin-Releasing Hormone Messenger Ribonucleic Acid Expression in the Paraventricular Nucleus of the Human Hypothalamus

Abstract: The way glucocorticoids affect TRH mRNA expression in the paraventricular nucleus of the hypothalamus is still unclear. In view of its relevance for Cushing's syndrome and depression, we measured TRH mRNA expression in human hypothalami obtained at autopsy by means of quantitative TRH mRNA in situ hybridization. In corticosteroid-treated subjects (n = 10), TRH mRNA hybridization signal was decreased as compared with matched control subjects (n = 10) (Mann-Whitney U test, P = 0.02). By inference, hypercortisoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 41 publications
2
45
0
1
Order By: Relevance
“…Adrenalectomy in rats increases pro-TRH mRNA levels in the PVN, whereas administration of exogenous corticosterone or dexamethasone to rats has the opposite effect (Kakucska et al, 1995). Similar effects appear to be at play in humans, since people that had been treated with glucocorticoids until the time of death showed a significant decrease in TRH mRNA levels in the PVN compared to control subjects (Alkemade et al, 2005), and glucocorticoid excess suppresses the secretion of TSH in humans (Nicoloff et al, 1970). In addition to glucocorticoids, the hypothalamo-pituitary-thyroid axis is regulated by insulin.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Adrenalectomy in rats increases pro-TRH mRNA levels in the PVN, whereas administration of exogenous corticosterone or dexamethasone to rats has the opposite effect (Kakucska et al, 1995). Similar effects appear to be at play in humans, since people that had been treated with glucocorticoids until the time of death showed a significant decrease in TRH mRNA levels in the PVN compared to control subjects (Alkemade et al, 2005), and glucocorticoid excess suppresses the secretion of TSH in humans (Nicoloff et al, 1970). In addition to glucocorticoids, the hypothalamo-pituitary-thyroid axis is regulated by insulin.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, whereas acute or chronic ICV NPY administration induced pronounced hypercorticosteronemia and hyperinsulinemia, HS014 induced a modest rise in corticosteronemia only during the first hour after acute ICV injection. As glucocorticoids inhibit activity of the thyrotropic axis (Kakucska et al, 1995, Alkemade et al, 2005and Nicoloff et al, 1970, this finding may contribute to the observed differences in effects of NPY versus HS014 on plasma TSH and free T4 concentrations. Despite these patent dissimilarities in hormonal responses to central administration of NPY or the MC4 receptor antagonist HS014, both peptides resulted in marked and significant increases in adiposity and leptinemia after chronic infusion, even though pair feeding with vehicle-infused control animals prevented NPY-and HS014-induced hyperphagia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preterm children therefore suffer from transient hypothyroxinemia, which may affect hypothalamic TH signaling (30,31,32). In addition, we cannot exclude effects of non-thyroidal illness or glucocorticoid treatment on protein expression levels (33,34). Strikingly, toward the end of gestation, TH transporters and D2 immunoreactivity decreased, whereas D3 expression increased.…”
Section: Discussionmentioning
confidence: 97%